Smart Goal Setting in Physical Therapy - Hertsyk, Andrii; Герцик, Андрій (Східноєвропейський національний університет імені Лесі Українки, 2016)
SMART format has been a common method of setting goals in the rehabilitation process. That is why the study of establishing SMART goals is included in the physical therapy curriculum. The experience demonstrates the need of simple and clear interpretation of SMART format to prepare physical therapists. Purpose. The purpose of this study was to analyze existing approaches of SMART goals formulations to choose one of the basic definitions of SMART format for educational needs and practice, and to offer a clear interpretation of selected definition. Method. Twenty different formulations of SMART format for general use and physical therapy were analyzed. The most common determinations have been identified and selected. Systemic analysis of definition combi- nations including links between them and the specific of physical therapy was performed. Results. In the selection of a SMART- format the following problems were identified, such as the large number of options, the repetition of the definitions based on their content, contradiction and inaccuracy and different inter- pretation of the same definitions.The main requirements of setting combination for SMART goals in the physical therapy were defined and the goal setting features were revealed. It is established, that the choice of definitions needs only in certain combinations based on the definitions interpretation and relationships between them. Systemic resources held by the physical therapist and the patient is defined to address the research objectives. An option of SMART format for use in physical therapy is justified. Conclusions. Students need to be taught to formulate the physical therapy goals in one option of the SMART goal format. The ideal format is impossible. The key questions for the correct goals setting are correct definition interpretation and accurate assessment of available resources. SMART-формат является распростра- ненным методом постановки целей в реабилитационном процессе. Именно поэтому изучение создания SMART- целей входит в учебную программу по физической реабилитации / терапии. Опыт показывает необходимость простой и понятной трактовки SMART-формата для подготовки фи- зических реабилитологов / терапевтов. Цель данного исследования – анализ существующих подходов к форму- лировке SMART-целей для выбора одного из основных определений SMART-формата для образовательных потребностей и практической деятель- ности, а также предложить четкое толкование выбранного определения. Методы. Проанализированы 20 ва- риантов формулировки SMART- формата для универсального примене- ния и физической реабилитации / тера- пии. Обнаружены и выделены распро- страненные определения. Выполнен системный анализ комбинаций опре- делений с учетом связей между ними и особенностей физической терапии. Результаты. В выборе SMART- формата выявлены следующие проб- лемы: большое количество вариантов, повторение определений по содержа- нию, противоречие и неточности, разная трактовка одинаковых опреде- лений. Установлены основные требования к комбинации определений для установления SMART-целей в фи- зической реабилитации / терапии и выявлены особенности постановки целей. Установлено, что выбор определений необходимо выполнять только в определенных комбинациях с учетом трактовки определений и связей между ними. Для решения зада- чи исследования определены систем- ные ресурсы, которыми обладают физический реабилитолог / терапевт и пациент. Обоснован вариант SMART- формата для применения в физической реабилитации / терапии. Выводы. Студентов целесообразно научить формулировать цели физической реабилитации / терапии в одном варианте SMART-формата. Не может быть идеального формата. Ключевыми вопросами для корректной постановки целей является правильная трактовка определений и точная оценка имеющихся ресурсов.
Постановка мети фізичної реабілітації / терапії в smart-форматі
Keywords: subsystems of physical therapy; system resources; підсистеми фізичної реабілітації / терапії; системні ресурси